SAT0353 Meta-Analysis Comparing the Efficacy of Tnf-Blockers in as and Nr-Axspa Patients. (10th June 2014) - Callhoff, J.; Sieper, J.; Weiß, A.; Zink, A.; Listing, J.
Abstract : Background: Tumor necrosis factor α (TNFα) blockers are known to reduce disease activity in patients with ankylosing spondylitis (AS). Data from a growing number of randomised controlled trials (RCTs) suggest them to be efficacious for patients with non-radiographic axial spondylarthritis (nr-axSpA), too. So far there is no meta-analyses comparing the efficacy of TNFα blockers between patients with AS and nr-axSpA. Objectives: In this meta-analysis we aimed to evaluate if TNFα blockers have a clinically meaningful effect on disease activity and function in patients with AS and nr-axSpA. It was also compared if there were differences in the efficacy of TNFα blockers between these patient groups. Methods: A systematic literature search in Pubmed and Web of Knowledge was performed to identify double blind randomized controlled trials (RCTs) comparing treatment with TNFα blockers in an approved dosage to placebo (and concomitant NSAIDs). We investigated the efficacy of TNFα blockers by assessing a) the standardized mean difference (SMD) in the outcome between verum and placebo and b) the odds ratio (OR) for ASAS40-response. In mixed effects meta-regression models the effect of the publication year was considered, and efficacy for AS and nr-axSpA patients was compared. Results: 21 studies with data from 3662 patients were included in the analysis: 16 studies with AS patients, 4 with nr-axSpA patients and one with both. There were 6 eligible studies with adalimumab, 1 with certolizumab, 8 with etanercept, 1 with golimumab and 5 with infliximab. For AS patients, TNFα blockers showed better efficacy than placebo for BASDAI (SMD 0.96, [95% CI: 0.83, 1.10]), BASFI (SMD 0.66, [0.59, 0.74]) and ASAS40 response (OR 4.3, [3.4, 5.4]). For nr-axSpA patients the differences were smaller (SMDs: 0.73, [95% CI: 0.44, 1.01], 0.59, [95% CI: 0.30, 0.88]; OR: 3.6, [95% CI: 2.5, 5.3]). Between 2000 and 2013 there was an overall trend to include AS patients with shorter symptom duration and less functional limitations in the RCTs. Taking this into account by including the year of publication as a proxy for disease severity in the statistical model we did not observe significant differences in the outcome (BASDAI, BASFI, ASAS40 response) between the AS and nr-axSpA trials. Conclusions: Compared to placebo, TNFα blockers improve disease activity and functional capacity clinically meaningful for both AS and nr-axSpA patients. We found only small and not significant differences in efficacy between these patient groups. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2902